Right ventricular systolic dysfunction at rest is not related to decreased exercise capacity in patients with a systemic right ventricle. (1st June 2018) - Helsen, Frederik; De Meester, Pieter; Van De Bruaene, Alexander; Gabriels, Charlien; Santens, Béatrice; Claeys, Mathias; Claessen, Guido; Goetschalckx, Kaatje; Buys, Roselien; Gewillig, Marc; Troost, Els; Voigt, Jens-Uwe; et al.
Abstract: Background: To evaluate the relationship between right ventricular (RV) systolic dysfunction at rest and reduced exercise capacity in patients with a systemic RV (sRV). Methods: All patients with congenitally corrected transposition of the great arteries (ccTGA) or complete TGA after atrial switch (TGA-Mustard/Senning) followed in our institution between July 2011 and September 2017 who underwent cardiac imaging within a six-month time period of cardiopulmonary exercise testing (CPET) were analyzed. We assessed sRV systolic function with TAPSE and fractional area change on echocardiogram and, if possible, with ejection fraction, global longitudinal and circumferential strain on cardiac magnetic resonance (CMR) imaging. Results: We studied 105 patients with an sRV (median age 34 [IQR 28–42] years, 29% ccTGA and 71% TGA-Mustard/Senning) of which 39% had either a pacemaker (n = 17), Eisenmenger physiology (n = 6), severe systemic atrioventricular valve regurgitation (n = 14), or peak exercise arterial oxygen saturation < 92% (n = 17). Most patients were asymptomatic or mildly symptomatic (NYHA class I/II/III in 71/23/6%). Sixty-four percent had evidence of moderate or severe sRV dysfunction on cardiac imaging. Mean peak oxygen uptake (pVO2) was 24.1 ± 7.4 mL/kg/min, corresponding to a percentage of predicted pVO2 (%ppVO2) of 69 ± 17%. No parameter of sRV systolic function as evaluated on echocardiography (n = 105) or CMR (n = 46) was correlated with the %ppVO2, even after adjusting for associated cardiac defects or pacemakers. Conclusions: In adults with an sRV, there is no relation between echocardiographic or CMR-derived sRV systolic function parameters at rest and peak oxygen uptake. Exercise imaging may be superior to evaluate whether sRV contractility limits exercise capacity. Highlights: Systemic right ventricular (sRV) dysfunction is common in paucisymptomatic adults with TGA after atrial switch or ccTGA. There seems to be no association between resting parameters of sRV systolic function and peak oxygen uptake. Regular follow-up should include exercise testing, even in paucisymptomatic adults with an sRV.